PENGGUNAAN TEKNIK FISHBONE DIGITAL BERBANTUAN CANVA DALAM PEMBELAJARAN MEMBACA SISWA SMP - Titi Hayati; Ika Mustika; Yeni Rostikawati (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research was conducted to investigate issues that arise in reading comprehension, such as difficulties students face in understanding the content of readings, especially novels, as well as difficulties in identifying and searching for the components of 5W+1H (what, where, when, who, why, and how). The research was carried out in the eighth grade of Budi Bakti Utama Junior High School. The aim of this research was to describe the use of the digital fishbone technique in reading instruction and to facilitate the identification of 5W+1H components in novels. The method employed in this study is quantitative descriptive, which aims to provide a clear and objective depiction of the reading comprehension outcomes in a measurable manner. The data collection technique in this research was in the form of a test. As for the data analysis technique, descriptive statistics were used. The results of the research showed that the use of the digital fishbone technique achieved an average score of 19,85 with a percentage of 86.30% categorized as good results. Therefore, reading instruction using the digital fishbone technique with the assistance of Canva can be considered successful, as students were able to achieve above-average percentage scores. These results prove that with the use of the digital fishbone technique, students can more easily comprehend and identify the content of the reading in novels.